The Reevaluation of MIBI as the Ligand of 99mTc-MIBI Radiopharmaceutical for Myocardial Imaging - Z. Nurlaila; I. Daruwati (PPIKSN-BATAN, 2008)
Methoxy isobutyl isonitrile labelled with technetium-99m (99mTc) radionuclide can be used for the evaluation of acute myocardial infarction. The 99mTc-MIBI radiopharmaceutical is available in the lyophilized-kit, which is separately packed with its radionuclide. Recently, in CNTMR-BATAN Bandung, 99mTc-MIBI radiopharmaceutical was prepared using MIBI ligand synthesized in 1996 as lyophilized-kits having the radiochemical purity less than 90 % and not accumulated in the myocardium. It could be caused by several factors, among others were technical preparation of lyophilized dry-kit and the quality of MIBI; therefore the reevaluation of the ligand for the quality improvement was needed. Firstly, MIBI ligand was recristallized. It was found that MIBI as [Cu(MIBI)4]BF4 salt was a glassy solid with the melting point of 98 -99 oC. The infra red analysis showed the presence of spectra vibration at 1085, 1180 cm-1 and 2180, 2220 cm-1 for –OCH3 and N≡C groups, respectively. The preparation of 99mTc-MIBI was performed by adding 99mTc radionuclide into new MIBI liquid-kit, then boiled in water bath for minimum period of 10 minutes. The radiochemical purity of 99mTc-MIBI was analysed by thin layer chromatographic method using absolute ethanol as a mobile phase. The pre-clinical evaluation was observed in Wistar rat and clinical studies were performed in volunter using gamma camera. It is revealed that the radiochemical purity of more than 90 % i.e. 96.83 ± 1.43 % was still stable until 24 hours storage at room temperature. The stability studies of 99mTc-MIBI in human blood plasma showed that in 6 hours, the radiochemical purity was decreased to 90.89 ± 2.90 %. Clinical application of 99mTc-MIBI with tomography techniques using gamma camera showed the distinct accumulation of radioactivity in the heart.